Post-engorgement dynamics of haemagglutination activity in the midgut of phlebotomine sandflies - Volf, P; Killick-Kendrick, R (Medical and veterinary entomology, 1996)
Haemagglutination activity (HA) was studied in gut extracts of both sexes of adults of six sandfly species. HA was sex dependent, with the activity in males more than 50 times lower than that of unfed females. In females, high HA was demonstrable in both the thoracic and abdominal midgut but not in the hindgut. In unfed flies the activity was similar in the midgut wall and the gut contents whereas, in fed females, a high increase was seen in the midgut contents. After blood-feeding, HA was elevated, reaching peak titres 2 days later and then falling to the base level or less immediately after defaecation. The magnitude of the HA response differed according to species, ranging from 2-fold in Lutzomyia carmelinoi up to 16-fold in Phlebotomus duboscqi. Quantitative differences between sandflies in their HA response may influence their ability to support the development of Leishmania spp.
Keywords: sexuální faktory; Sex Factors; Phlebotomus; Female; Leishmania; Animals; ženské pohlaví; mužské pohlaví; Psychodidae; Male; trávení; hemaglutinace; zvířata; Hemagglutination; Digestion